Young‐onset diabetes patients in Thailand: Data from Thai Type 1 Diabetes and Diabetes diagnosed Age before 30 years Registry, Care and Network (T1DDAR CN). Issue 5 (6th January 2022) - Dejkhamron, Prapai; Santiprabhob, Jeerunda; Likitmaskul, Supawadee; Deerochanawong, Chaicharn; Rawdaree, Petch; Tharavanij, Thipaporn; Reutrakul, Sirimon; Kongkanka, Chawkaew; Suprasongsin, Chittiwat; Numbenjapon, Nawaporn; Sahakitrungruang, Taninee; Lertwattanarak, Raweewan; et al.
ABSTRACT: Aims/Introduction: There is a lack of current information regarding young‐onset diabetes in Thailand. Thus, the objectives of this study were to describe the types of diabetes, the clinical characteristics, the treatment regimens and achievement of glycemic control in Thai patients with young‐onset diabetes. Materials and Methods: Data of 2, 844 patients with diabetes onset before 30 years‐of‐age were retrospectively reviewed from a diabetes registry comprising 31 hospitals in Thailand. Gestational diabetes was excluded. Results: Based on clinical criteria, type 1 diabetes was identified in 62.6% of patients, type 2 diabetes in 30.7%, neonatal diabetes in 0.8%, other monogenic diabetes in 1.7%, secondary diabetes in 3.0%, genetic syndromes associated with diabetes in 0.9% and other types of diabetes in 0.4%. Type 1 diabetes accounted for 72.3% of patients with age of onset <20 years. The proportion of type 2 diabetes was 61.0% of patients with age of onset from 20 to <30 years. Intensive insulin treatment was prescribed to 55.2% of type 1 diabetes patients. Oral antidiabetic agent alone was used in 50.8% of type 2 diabetes patients, whereas 44.1% received insulin treatment. Most monogenic diabetes, secondary diabetes and genetic syndromes associated with diabetes required insulin treatment. Achievement of glycemic control was identified in 12.4% of type 1 diabetes patients, 30% of type 2 diabetes patients, 36.4% of neonatal diabetes patients, 28.3% of other monogenic diabetes patients, 45.6% of secondary diabetes patients and 28% of genetic syndromes associated with diabetes patients. Conclusion: In this registry, type 1 diabetes remains the most common type and the prevalence of type 2 diabetes increases with age. The majority of patients did not achieve the glycemic target, especially type 1 diabetes patients. Abstract : This is a diabetes registry comprising 31 hospitals in Thailand. Type 1 diabetes remains the most common type, and the prevalence of type 2 diabetes increases with age. The majority of patients did not achieve the glycemic target, especially type 1 diabetes patients.